Russia : Policies for Agri-Food Sector Competitiveness and Investment - World Bank Group (World Bank, Washington, DC, 2017)
Despite advances in agricultural production, TFP, and trade balances, Russia continues to lag behind many comparator countries in measures of crop and livestock productivity. This report has aimed to provide a vehicle for dialogue with government on agri-food sector collaboration to address this situation. It has identified policy recommendations to address selected challenges and to support the government's aim of attracting investments in the agri-food sector, approached from the point of view that increased productivity will improve the competitiveness of agri-food value chains, result in higher profitability, and encourage more investment, including FDI, in Russian agriculture. In practical terms, this report has identified three areas in which the public sector may be able to use policy and programmatic interventions to spur productivity, competitiveness, investment, and exports: investing in broadening productivity gains in priority sectors, strengthening value chains and value-addition in the food industry, and promoting human capital in rural areas through capacity building in agricultural sciences and farm management to improve labor productivity. Some progress has been made, but more is needed.